Does ridesharing affect road safety? the introduction of Moto-Uber and other factors in the Dominican Republic - José Ignacio Nazif-Munoz; Brice Batomen; Arijit Nandi (Research in Globalization, 2022)
Background: Annually, more than 379 000 motorcycle occupants across the world die in motor-vehicle collisions—84% of these fatalities occurred in Low- and Middle-Income countries. Recent studies suggest that the Uber’s four-wheeler ride-sharing service (UberCAR) may reduce traffic fatalities. However, research has not considered how Uber’s two-wheeler ridesharing service (UberMOTO) might affect traffic-motorcycle fatalities. Methods: Monthly counts of car occupant and motorcycle fatalities from the Dominican Republic, a country in which both Uber services have been introduced, were collected from the Ministry of Public Health. We conducted interrupted time-series analyses using monthly traffic fatalities per 100,000 population for the period 2012–2018. We studied Santo Domingo and Santiago, the only two cities in which UberCAR and UberMOTO were launched in different times. Results: The introduction of UberMOTO was associated with a 0.16 short-term decrease (95% CI -0.29 to −0.05) in the level of monthly motorcycle fatalities per 100,000 population in Santo Domingo, and a 0.34 decrease (95% CI −0.68, 0.00) in Santiago. UberCAR was associated with an increase of 0.03 (95% CI −0.06 to 0.13) in the level of monthly car occupant fatalities per 100,000 population in Santo Domingo, and with a 0.20 increase (95% CI 0.05 to 0.35) in Santiago. Conclusion: After Santo Domingo and Santiago introduced UberMOTO and UberCAR services, we observed short-term decreases in motorcycle fatalities and abrupt increases in car fatalities, respectively. These associations of ridesharing services with traffic fatalities vary between cities and over time, which might reflect differences in specific city features, including characteristics of the vehicle fleet and public transportation systems.